Financial well-being for sustainable development goals (SDGs): family as the foundation - Ghazali, Mohd Samsuri; Syed Alwi, Sharifah Faigah; Idris, Nur Hafidzah; Sabri, Mohamad Fazli; Abd Aziz, Nurul Nadia (Universiti Malaysia Terengganu, 2023)
This study aims to evaluate the influence of parents (explicit and implicit) on the financial well-being of emerging adult workers in Malaysia. At the same time, this study will also examine if financial behaviour can mediate between parental influence and financial well-being. Respondents aged 19 to 29 from Sabah, Pahang, Perak, Selangor, and Melaka answered 500 survey-based online questions. The hypothetical model was statistically tested via Partial Least Square (SmartPLS) version 3.3.2. Results show that both implicit and explicit features of family financial socialisation considerably impact emerging adults financial conduct. However, implicit factors significantly impact emerging adults financial conduct more than explicit factors. Results also confirm the role of financial behaviours as a mediator between the influence of parents and the financial well-being of emerging adults. Therefore, this study supports the hypothesis that parental effects extend beyond infancy to emerging adulthood. Parents may aid their children by demonstrating and imitating healthy financial behaviours and directing and guiding them. The requirement of boosting financial well-being to meet the SDGs goals is stressed in this study since the financial component is vital to success.